2020
DOI: 10.1111/aogs.13953
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal and perioperative factors associated with mortality and an increased need for hospital care in infants with transposition of the great arteries: A nationwide 11‐year population‐based cohort

Abstract: Introduction: Newborn infants with transposition of the great arteries (d-TGA) need immediate care for an optimal outcome. This study comprised a nationwide 11-year population-based cohort of d-TGA infants, and assessed whether the implementation of a nationwide systematic fetal screening program, or other perinatal, or perioperative factors, are associated with mortality or an increased need for hospital care. Material and methods: The national cohort consisted of all live-born infants with simple d-TGA (TGA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
1
4
0
1
Order By: Relevance
“…From a national cohort of all live‐born infants with simple d‐TGA (TGA ± small ventricular septal defect, n = 127) born in Finland during 2004–2014 (Hautala et al, 2020), we identified live‐born cases for whom register data and Biobank serum samples were available ( n = 100). Each case was matched with two healthy controls ( n = 200) according to the sex of the child, year of birth, and the age and the body mass index (BMI) of the mother as well as Biobank sample availability.…”
Section: Methodsmentioning
confidence: 99%
“…From a national cohort of all live‐born infants with simple d‐TGA (TGA ± small ventricular septal defect, n = 127) born in Finland during 2004–2014 (Hautala et al, 2020), we identified live‐born cases for whom register data and Biobank serum samples were available ( n = 100). Each case was matched with two healthy controls ( n = 200) according to the sex of the child, year of birth, and the age and the body mass index (BMI) of the mother as well as Biobank sample availability.…”
Section: Methodsmentioning
confidence: 99%
“…These screening serum samples collected over the years 1983-2016 (Finnish Maternity Cohort) were deposited at Biobank Borealis if the mother consented to this (15). From a national cohort of all live-born infants with simple d-TGA (TGA +/-small ventricular septal defect, n=127) born in Finland during 2004-2014 (16) , we identified 100 live-born cases and each case was matched with two healthy controls (n=200) whose maternal screening samples were available at Biobank Borealis. The background data was collected from the Medical Birth Register maintained by the Finnish Institute for Health and Welfare.…”
Section: Methodsmentioning
confidence: 99%
“…A realização de um diagnóstico pré-natal possibilita a centralização do parto dos neonatos portadores de TGA em locais com nível de complexidade adequado para o gerenciamento ideal da DCC apresentada (HAUTALA et al, 2020). Assim, o diagnóstico pré-natal da TGA possui benefícios significativos contribuindo para melhores condições de pré-operatório e resultados cirúrgicos.…”
Section: Importância Do Diagnóstico Precoceunclassified